Une archéologie de la ville. À partir des « espaces autres » de Michel Foucault - Alessandro Zinna (Ocula)
The conference on heterotopias is an opportunity to propose an urban and social archaeology. The article suggests a genealogy of the city through the ar-rangement of four spaces: topic, heterotopic, utopic and homotopic. Another fragment of this lecture in-troduces the virtual space of the mirror. This rein-terpretation anticipates modernity's own hybridisa-tion between topical and a-topical spaces. It becomes an opportunity to question the access and alternative presence of a situated subject in these Euclidean and non-Euclidean spaces. We conclude with some con-siderations on the organisation of space and sociali-ty a50 years after the reflection initiated by Foucault.